Безпечність зберігання ключів у EVM-блокчейнах - Зражевець, К. П. (ХНУРЕ, 2023)
This work is an overview of various solutions for storing and securing private keys in EVM-compatible blockchains. It discusses hardware wallets, which are physical devices storing private keys in a secure environment, hot wallets that store keys on internet-connected devices, and cold wallets that store keys on devices without constant internet connection. The text also covers multi-signature technology, which requires signatures from multiple parties to execute a transaction, and protocol-level security mechanisms that utilize asymmetric encryption or distributed key storage. Additionally, the importance of backup and restoration of keys, different access levels, two-factor authentication, regular software updates, and risk management is addressed